Diagnostic and therapeutic challenges in a case of disseminated parasitic, metastatic, peritoneal and peritoneal leiomyomatosis: a complex approach - Aranaz Murillo, Amalia (2024)
We describe a case presenting a rare combination of parasitic, metastasizing anddisseminated peritoneal leiomyomatosis, challenging diagnosis and treatment. Thepatient initially presented with symptoms related to compression of pelvic structures,followed by the appearance of leiomyomas in the abdominal wall and finallyleiomyomas distributed throughout the peritoneum and eventually associated withascites. The differential diagnosis is broad and complex and includes metastasesof primary tumors, among others. Moreover, the lack of a standard of treatmentunderlines the complexity of these pathologies, advocating a comprehensive surgicalapproach and considering pharmacological treatment options if there is gestationaldesire.